Postharvest dormancy-related changes of endogenous hormones in relation to different dormancy-breaking methods of potato (Solanum tuberosum L.) tubers - Haider, Muhammad Wasim; Nafees, Muhammad; Ahmad, Ishtiaq; Ali, Baber; Maryam,; Iqbal, Rashid; Vodnar, Dan C.; Marc, Romina Alina; Kamran, Muhammad; Saleem, Muhammad Hamzah; Al-Ghamdi, Abdullah Ahmed; Al-Hemaid, Fahad M.; et al. (Frontiers in Plant Science, 2022)
In potato (Solanum tuberosum L.), developing an efficient and eco-friendly technique for breaking tuber dormancy is highly demanded due to the production of two or more crops per year in Punjab or all over Pakistan. Its tubers go through a period of dormancy after harvest and are unable to sprout, limiting their use as seed for the following season. In fact, a number of physiological and hormonal changes have been found to be related to the breaking of tuber dormancy, however, their consistency with genotypes and different protocols have not been well clarified. The present study aims to evaluate the effectiveness of four dormancy breaking methods,i.e., plant growth regulator (PGR) dipping in 30, 60, or 90 mgL-1 benzyl amino purine (BAP) and 10, 20, or 30 mgL-1 gibberellic acids (GA3) alone and in the combination of optimized concentrations; electric current application at 20, 40, 60, or 80 Vs; cold pre-treatment at 2, 4, or 6°C; irradiation at 1,-3.5 kGy. In addition, changes in endogenous levels of abscisic acid (ABA), zeatin (ZT), and gibberellin A1 (GA1) in six potato genotypes after subjecting to these methods were investigated. Overall, the highest effective method for dormancy duration was the PGR application which shortened the duration by 18 days, followed by electric current (13 days), cold pre-treatment (9 days), and then irradiation. The solution of 60 mgL-1BAP significantly reduced the dormancy duration in all genotypes but did not have a significant effect on the sprout length. While 20 mgL-1 GA3 produced maximum sprout length with a non-significant effect on dormancy duration. The genotype × PGR interaction for dormancy duration was more pronounced in short and medium-term dormancy genotypes than in long-term dormancy genotypes. The genotypes displayed a significant positive correlation between dormancy duration and ABA levels but gave a negative correlation between dormancy duration and ZT as well as GA1 levels. From the first to the third week of storage, ABA decreased in tubers and by contrast, ZT and GA1 increased in tubers. These results might be useful for the postharvest storage of potato tuber and the related field of physiological investigation in future.